Manet a model family - Greenwald, Diana Seave 1989-; Als, Hilton 1960-; Wilson-Bareau, Juliet 1935-; Beeny, Emily A. 1982-; Kremnitzer, Kathryn; Pludermacher, Isolde; Locke, Nancy 1963- (Isabella Stewart Gardner Museum, 2024)
"A groundbreaking and richly illustrated account of the importance of Manet's family to his artAll families are complicated, but the family of Édouard Manet (1832-1883) was more complicated than most. The artist married his father's alleged mistress-whose son, born out of wedlock, may have been Édouard's, his father's, or another man's. For all its complexities, Manet's family fueled his creativity. They were his most frequent models, and supported him emotionally and financially. Manet: A Model Family is an innovative new exploration of the largely neglected story of the importance of Manet's family to his art.Presenting new research on works in which Manet depicted family members, Manet: A Model Family shows how an understanding of the artist's family sheds crucial light on his artistic career. Manet's mother, wife, stepson, and other relatives-including his sister-in-law, the painter Berthe Morisot-are given long overdue recognition for their role in Manet's life and work. Leading scholars present technical and archival analysis, including redating Madame Auguste Manet, an important, newly conserved painting of Manet's mother. In an essay inspired by that canvas, Pulitzer Prize-winning critic Hilton Als reconsiders Manet's formative relationship with his mother and his bourgeois Parisian roots.With its original account of Manet's domestic relationships and personal life, Manet: A Model Family humanizes the artist and his contributions to the birth of modernism."
Impressum: "First published to accompany the exhibition "Manet: A Model Family" ... at the Isabella Stewart Gardner Museum, Boston, October 10, 2024 - January 20, 2025"
Keywords: Manet, Edouard -- 1832-1883; Manet, Édouard / 1832-1883 / Exhibitions; Manet, Édouard / 1832-1883 / Family / Portraits / Exhibitions; ART / Individual Artists / General; ART / European; Manet, Édouard / 1832-1883; Families; Portraits; Ausstellungskatalog -- Isabella Stewart Gardner Museum -- 10.10.2024-20.01.2025 -- Boston, Mass.